The Ability of Ginger Rhizome (Zingiber officinale Rosc) Extract in Producing of Silver Nanoparticles and the Antibacterial activity of these nanoparticles - Thi Phuong, Ho; Thi Le Na, Nguyen; Trung Thanh, Nguyen; Dinh Thang, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 3DO - 10.25073/2588-1140/vnunst.4922, 2019)
Recently, using plant extract as a reducing agent for nanosilver particle synthesis has been focused. This is a green technology utilizing the ready material in the nature to create the nanoparticles with good properties and uniqe quality. In this study, ginger rhizome extract was used to reduce the silver cation (Ag + ) to silver (Ag o ) as nanoparticles with uniqe quality and even distribution in the solution. The size of the particles varied in the range of 20-40 nm. Reaction conditions were investigated and optimized with AgNO 3 concentration of 3mM, extract solution/AgNO 3 solution of 1/5, temperature of 80˚C, pH of 12 and reaction time of 30 min. The results obtained from the antibacterial assays showed that silver nanoparticle solution had antibacterial ability with an average effective diameter of 10 mm. It also indicated that the antibacterial activity of silver nanoparticle solution on the Gram (-) bacterium (E. coli) is better that on Gram (+) bacterium (S. aureus). In conclusion, we suggest that the ginger rhizome extract can be used to produce silver nanoparticles in mild reaction conditions; the silver nanoparticle solution expressed as a quite good antibacterial agent and therefore could be applied in decreasing the effects of deleterious bacteria. Keywords Silver nanoparticle, plant extract, antibacterial, Zingiber officinale Rosc. References [1] L.S. Li, J. Hu, W. Yang and P. Alivisatos. Band gap variation of size- and shape-controlled colloidal CdSe quantum rods. Nano Lett. 1(2001) 49-51. https://doi.org/10.1021/nl015559r. [2] A. P. Nikalje. Nanotechnology and its Applications in Medicine. Medicinal chemistry, 5(2015) 81-89. [3] G. Doria, J. Conde, B. Veigas et al. Noble metal nanoparticles for biosensing applications. Sensors 12(2012) 1657–1687. https://doi.org/ 10.4172/2161 -0444.1000247 [4] A. J. Haes, A. D. McFarlan, R. P. van Duyne. Nanoparticle optics: sensing with nanoparticle arrays and single nanoparticles. The International Society for Optical Engineering 5223 (2003) 197–207. https://doi.org/10.1039/C7NR03311G. [5] A. Elham, M. Morteza, F. V. Sedigheh, K. Mohammad, A. Abolfazl, T. N. Hamid, N. Parisa, W. J. San, H. Younes, N-K. Kazem, S. Mohammad. Silver nanoparticcles: Synthesis methods, bio-applications and properties. Critical reviews in Microbiology 42(2016) 173-180. https://doi.org/10.3109/1040841X.2014.912200. [6] J. K. Pradeep, K. Chaudhury, V. S. Suresh, K. G. Sujoy. An emerging interface between life science and nanotechnology: present status and prospects of reproductive healthcare aided by nano-biotechnology. Nano Rev. 5(2014): 10.3402/ nano. v5. 22762. https://doi.org/10.3402/nano.v5.22762. [7] M. Danilcauk, A. Lund, J. Saldo, H. Yamada, J. Michalik. Conduction electron spin resonance of small silver particles. Spectrochimaca. Acta. Part A 63(2006) 189–191. https://doi.org/10.1016/j.saa. 2005.05.002 [8] J. L. Elechiguerra, J. L. Burt, J. R. Morones et al. Interaction of silver nanoparticles with HIV-1. Journal of Nanobiotechnology 3(2005) 6. https:// doi.org/10.1186/1477-3155-3-6 [9] J. S. Kim, E. Kuk, K. Yu, J. H. Kim, S. J. Park, H. J. Lee, S. H. Kim, Y. K. Park, Y. H. Park, C. Y. Hwang, Y. K. Kim, Y. S. Lee, D. H. Jeong, M. H. Cho. Antimicrobial effects of silver nanoparticles. Nanomedicine 3(2007) 95–101. https://doi.org/ 10.1016/j.nano.2006.12.001. [10] Y. Matsumura, K. Yoshikata, S. Kunisaki and T. Tsuchido. Mode of bacterial action of silver zeolite and its comparison with that of silver nitrate. Appl. Environ. Microbiol. 69(2003) 4278–4281.https://doi.org/10.1128/AEM.69.7.4278-4281. 2003. [11] M. Yamanaka, K. Hara, J. Kudo. Bactericidal Actions of a Silver Ion Solution on Escherichia coli, Studied by Energy-Filtering Transmission Electron Microscopy and Proteomic Analysis. Appl. Environ. Microbiol. 71(2005) 7589–7593. https://doi.org/10.1128/AEM.71.11.7589-7593. 2005. [12] Y. H. Hsueh, K. S. Lin, W. J. Ke, C. T. Hsieh, C. L. Chiang, D. Y. Tzou and S. T. Liu. The Antimicrobial Properties of Silver Nanoparticles in Bacillus subtilis Are Mediated by Released Ag+ Ions. PLoS One 10(2015):e0144306. https://doi.org/10.1371/journal.pone.0144306. [13] N. Kumar, S. Das, A. Jyoti and S. Kaushik. Synergistic effect of silver nanoparticles with doxycycline against Klebsiella pneumoniae. Int. J. Pharm. Sci. 8(2016) 183-186. [14] V. G. Borodina, Y. A. Mirgorod. Kinetics and Mechanism of Interaction between HAuCl4 and Rutin. Kinet. Cat. 55(2014) 683–687. https://doi. org/10.1134/S0023158414060044. [15] V. V. Makarov, A. J. Love, O. V. Sinitsyna, S. S. Makarova, I. V. Yaminsky, M. E. Taliansky, N. O. Kalinina. Green nanotechnologies: synthesis of metal nanoparticles using plants. Acta Naturae 6(2014) 35–44. https://doi.org/10.1039/C1GC15 386B. [16] M. S. Butt, M. T. Sultan. Ginger and its health claims: molecular aspects. Critical Reviews in Food Science and Nutrition 51(2011) 383–393. https://doi.org/10.1080/10408391003624848 [17] M. Park, J. Bae, D. S. Lee. Antibacterial activity of gingerol and gingerol isolated from ginger rhizome against periodontal bacterial. Phytotherapy Research 22(2008) 1446–1449. https://doi.org/10.1002/ptr.2473 [18] Y. Shukla, M. Singh. Cancer preventive properties of ginger: a brief review. Food and Chemical Toxicology 45(2007) 683–690. https://doi.org/10. 1016/j.fct.2006.11.002.